Slide-Down Prevention for Wheeled Mobile Robots on Slopes - Martínez, Jorge L.; Mandow, Anthony; García-Cerezo, Alfonso José; García, Jesús M. (Springer, 2017)
Wheeled mobile robots on inclined terrain can slide down due to loss of traction and gravity. This type of instability, which is different from tip-over, can provoke uncontrolled motion or get the vehicle stuck. This paper proposes slide-down prevention by real-time computation of a straightforward stability margin for a given ground-wheel friction coefficient. This margin is applied to the case study of Lazaro, a hybrid skid-steer mobile robot with caster-leg mechanism that allows tests with four or five wheel contact points. Experimental results for both ADAMS simulations and the actual vehicle demonstrate the effectiveness of the proposed approach.
Keywords: Robots autónomos; mobile robots; slide-down; slopes